Services Provided for Lactating Mothers at Lactation Management Clinic in Selected Tertiary Level Hospitals: Services provided for lactating mothers (Journal of Preventive and Social Medicine, 2020)
Background: Children are the precious gift from the Almightily Allah and breast milk is an ideal product given to the human being by nature to fulfill all requirements of the offspring until they are matured enough to take adult food.Objective: To assess the services provided for lactating mothers at lactation management centre in selected tertiary level hospitals.Materials and Methods: This cross sectional study was conducted among 100 Lactating mothers who were selected conveniently and were interviewed by pre-tested semi-structured questionnaire and an observational checklist. Collected data were processed and analyzed using SPSS (Statistical Packages for Social Science) software.Results: Lactation management centre (LMC) is supervised by a consultant and separate room is allotted in both out-patient and in-patient departments. Mothers came with lactation problems were more likely in the first month of the baby (73%) and feeling of not enough milk production was common (49%).Highly significant relationship was found between breast problems of lactating mother and age of child (p